IMPLEMENTATION OF PARTICIPATORY RURAL APPRAISAL TO ASSIST THE ADMISSION OF NEW STUDENTS AT SALAFIYAH SYAFI'IYAH ISLAMIC BOARDING SCHOOL SUKOREJO SITUBONDO - Ahmad Homaidi; Lukman Fakih Lidimilah; Zaehol Fatah (LP2M Universitas Ibrahimy, 2020)
The acceptance of new information technology-based islamic students at the Salafiyah Syafi'iyah Sukorejo Situbondo Islamic Boarding School still needs assistance because not all of the human resources who are assigned to the committee for new santri have expertise in the field of information technology. Implementation of assistance using Participatory Rural Appraisal (PRA) with the aim that all parties play an active role in analyzing and solving problems. Based on the problems faced since the implementation of new islamic students admissions in 2017, the mentoring facilitators then took the initiative to conduct a discussion forum to reconsider and build idealism between policy makers and users regarding the new santri acceptance model using information technology. The facilitator provides an overview of the system that is running, and explains the weak points and what should be developed in what parts. Then the leaders and policy holders as well as users in the field were asked to convey what they had in mind regarding the implementation of the acceptance of new students. From here comes the absorption of aspirations from the musyawirin present at the forum, this is what is expected from the implementation of PRA, namely encouraging the community to take part in making improvements and analyzing the development of the implementation of new santri admissions and providing input in system development to suit the direction of development.